NEOADJUVANT CHEMOTHERAPY FOR LOCALLY ADVANCED CERVICAL CANCER - O. N. Churuksaeva; K. A. Kolomiets (Сибирский онкологический журнал)
Different modes of treatment of 78 patients with stage IIb-IIIb locally advanced cervical cancer were assessed. The study group comprised 30 patients who received 2 courses of neoadjuvant chemotherapy followed by combined curative radiation therapy. The comparison group included 20 patients who received combined radiation therapy with cisplatin radiomodification. The control group consisted of 28 patients who received combined curative radiation therapy. Neoadjuvant chemotherapy was found to promote more rapid symptom relief, significant reduction in primary tumor volume and improvement of tumor resectability. The assessment of long-term outcomes showed a significantincrease in recurrence-free and overall survival rates in patients treated with neoadjuvant chemotherapy compared to patients treated with radiation therapy without adjuvant chemotherapy. Neoadjuvant chemotherapy resulted in more pronounced positive changes in values of functional scale as well as in significant improvement of general health status of patients compared to other group patients